TWO-POINT PROBLEM FOR HOMOGENEOUS PARTIAL DIFFERENTIAL EQUATION IN UNBOUNDED STRIP - Volyanska, I. I.; Symotyuk, M. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
Well-posedness conditions of a two-point boundary-value problem are obtained for a high-order linear partial differential equation in an unbounded strip when the real parts of the roots of its characteristic equation are different.